Development of a high-yield expression and purification system for platelet factor 4. (3rd April 2018) - Huynh, Angela; Arnold, Donald M.; Moore, Jane C.; Smith, James W.; Kelton, John G.; Nazy, Ishac
Abstract: Heparin-induced thrombocytopenia (HIT) is an adverse drug reaction characterized by IgG antibodies bound to complexes of platelet factor 4 (PF4) and heparin. The majority of diagnostic tests for HIT rely on an exogenous source of PF4 to identify anti-PF4/heparin antibodies. These include the PF4-dependent enhanced serotonin release assay (PF4-SRA) among others. Using a bacterial expression system, we developed a novel and efficient method of producing recombinant human PF4 (rhPF4) that is biochemically and antigenically similar to platelet-derived human PF4. rhPF4 was produced using the pET expression system in the BL21(DE3) strain of Escherichia coli . The system was optimized for protein expression using isopropyl β-D-1-thiogalactopyranoside at different induction temperatures and incubation times. rhPF4 solubility was improved by using different detergents during cell lysis and by purifying with heparin affinity and ion exchange chromatography. Biochemical characteristics of rhPF4 were investigated using mass spectrometry, SDS-PAGE analysis, and gel filtration chromatography and compared to platelet-derived PF4. Antigenic and functional characteristics of rhPF4 were studied using the anti-PF4/heparin EIA and the PF4-SRA. Using this method, we could produce 11.4 ± 0.6 mg of pure rhPF4 per liter of bacterial culture. Absorbance readings from the anti-PF4/heparin EIA using platelet-derived and rhPF4 were highly correlated ( n = 194; r = 0.9545, p < 0.0001); and functional release of serotonin in the PF4-SRA induced by anti-PF4/heparin antibodies was similar to either platelet-derived or rhPF4 and heparin ( r = 0.9597, p < 0.0001). Our method of rhPF4 production is efficient and does not rely on a source of platelets. The rhPF4 purification method described produces greater yields at a lower cost than other current methods. The application of this method can improve the efficiency of biochemical investigations and HIT diagnostic testing by supplying sufficient amounts of PF4.